Redox chemistry and group 10 metal complexes of aromatic compounds with bulky bicyclic guanidino groups - Wild, Ute; Kaifer, Elisabeth; Himmel, Hans-Jörg (European journal of inorganic chemistry, 2011)
The reaction between activated bicyclic tetramethylbisurea and 1,2-diaminobenzene or 1,2,4,5-tetraaminobenzene affords new aromatic compounds functionalized with bicyclic guanidino groups. Protonation and redox reactions are carried out to obtain information about the chemical properties of these new guanidines. They are used as chelating ligands in mononuclear and dinuclear group 10 metal (Ni, Pd, and Pt) complexes, which could be interesting for catalytic applications. Initial experiments with a Ni complex showed a moderate activity in olefin oligomerization yielding mostly C6 hydrocarbons.
Gesehen am 03.11.2022